2012
DOI: 10.1016/j.ijgo.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and feasibility of laparoscopic sacrocolpopexy among obese versus non‐obese women

Abstract: Laparoscopic sacrocolpopexy has similar complication rates and short-term outcomes among both obese and non-obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…A low rate of complications among obese patients and good anatomic results after a short-term follow-up were found. 21,22 In the present study, the operating time was the same in both groups: 220 vs 200 min in the obese and non-obese groups, respectively (P=0.232). Two retrospective studies have already evaluated the technical feasibility of sacrocolpopexy by laparotomy and also laparoscopy among obese patients.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…A low rate of complications among obese patients and good anatomic results after a short-term follow-up were found. 21,22 In the present study, the operating time was the same in both groups: 220 vs 200 min in the obese and non-obese groups, respectively (P=0.232). Two retrospective studies have already evaluated the technical feasibility of sacrocolpopexy by laparotomy and also laparoscopy among obese patients.…”
Section: Discussionsupporting
confidence: 46%
“…Two retrospective studies have already evaluated the technical feasibility of sacrocolpopexy by laparotomy and also laparoscopy among obese patients. 21,22 Both techniques are available for obese women: the only difference is length of surgery. Considering the laparotomy approach, Bradley et al 21 found that operating times were significantly longer for obese women than non-obese women (189 vs 169 min; P=0.02).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations